Prevalence and Determinant Factors of Depression among Pregnant Women in PONED Health Center in Tangerang City Area - Hayati, Dian Geumala; Kamso, Sudijanto; Yuniar, Popy; Devi, Yuli Puspita (UI Scholars Hub, 2026)
According to World Health Organization (WHO), approximately 10% of pregnant women experience mental disorders, with depression being particularly prevalent. In developing countries, this rate is was even higher, reaching 19.8% after childbirth and 15.6% during pregnancy. Various studies conducted in Indonesia show that the prevalence of depression among pregnant women ranges widely, from 21.4% to 26.2%.This study aimed to determine the prevalence and risk factors associated with depression during pregnancy in pregnant women at the PONED Community Health Center in Tangerang City Area. A facility-based cross-sectional study was conducted with 105 pregnant women attending antenatal check-ups at the 17 PONED Community Health Center in Tangerang City in October 2024. The sample was obtained with a consecutive sampling technique. Information regarding sociodemographic, obstetric, and psychosocial factors was collected through questionnaires. Depression was assessed using the Edinburgh Postnatal Depression Scale (EPDS), a valid and reliable tool for screening depression in pregnant women. Univariate analysis was employed to determine the prevalence of depression and the characteristics of the pregnant women, bivariate analysis using the chi-square test, and multivariate analysis with a logistic regression model. The research findings revealed that the prevalence of depression among pregnant women was 22%(95% CI: 14%-30%). The most significant factor associated with depression was a history of stress due to life events (p-value = 0.004). Respondents with a history of stress were 8.6 times more likely to develop depression compared to those without such a history, even after adjusting for variables such as gravida, age, occupation, and income (Adjusted Odds Ratio = 8.62; 95% CI 2.03 – 36.69). This highlights the importance of screening for depression during antenatal care to identify and prevent further morbidityand mortality wrelated to antenatal depression. Keywords: Antenatal depression, mental health, pregnant women, risk factors, history of stress, EPDS